(untitled) (Our Nature, 2007)
Bantar, one of the dominant ethnic groups of Morang district is ethno botanically very rich. 98 species of plants belonging to 89 genera and 45 families used by Bantar as traditional medicines for human and domestic animals have been documented here. Ethno medication in most instances involves mantras alongside herbal application. Most diseases are treated by the use of more than one plant species while a single plant species is found to be used in curing more than one disease. Key words: Bantar, Ethno-medicinal plants, Morang doi:10.3126/on.v4i1.508 Our Nature Vol. 4(1) 2006 pp96-103